Emerging technologies for food processing - Sun, Da-Wen (Food Science and Technology)
The second edition of Emerging Technologies in Food Processing presents essential, authoritative, and completeliterature and research data from the past ten years. It is a complete resource offering the latest technological innovations in food processing today, and includes vital information in research and development for the food processing industry. It covers the latest advances in non- thermal processing including high pressure, pulsed electric fields, radiofrequency, high intensity pulsed light, ultrasound, irradiation, and addresses the newest hurdles in technology where extensive resea